1989
DOI: 10.1093/milmed/154.8.399
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Psychiatric Illness in Inpatients with Post-traumatic Stress Disorder

Abstract: The discharge diagnoses of 374 inpatients on a VA Medical Center general psychiatry ward were reviewed. Sixty-three (16.8%) were diagnosed as having posttraumatic stress disorder (PTSD). The mean number of diagnoses was 2.9 for the PTSD group, compared with 1.4 for the non-PTSD patients. The most common comorbid conditions in the PTSD patients were alcohol abuse, unipolar major depression, substance abuse, atypical psychosis, and intermittent explosive disorder. All of these disorders except substance abuse oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Other studies have demonstrated a significant association between substance abuse and being a victim of sexual abuse, both during childhood and adulthood (Wallace, 1991; Paone et aZ., 1992; Dembo et af., 1988). Given the prevalence of such victimization among women substance abusers, comorbidity of addictive disorders and PTSD would appear to be highly likely.A number of studies have examined rates of comorbidity of PTSD and substance abuse (Boudewyns et al, 1991; Hyer et aI., 1991; McFafl et al., 1991;Breslau et al, 1991;Breslau and Davis, 1987;Druley and Pashko, 1988;Hryvniak and Rosse, 1989;Kulka et al, 1990). Several findings emerge from these studies.…”
mentioning
confidence: 99%
“…Other studies have demonstrated a significant association between substance abuse and being a victim of sexual abuse, both during childhood and adulthood (Wallace, 1991; Paone et aZ., 1992; Dembo et af., 1988). Given the prevalence of such victimization among women substance abusers, comorbidity of addictive disorders and PTSD would appear to be highly likely.A number of studies have examined rates of comorbidity of PTSD and substance abuse (Boudewyns et al, 1991; Hyer et aI., 1991; McFafl et al., 1991;Breslau et al, 1991;Breslau and Davis, 1987;Druley and Pashko, 1988;Hryvniak and Rosse, 1989;Kulka et al, 1990). Several findings emerge from these studies.…”
mentioning
confidence: 99%
“…Divorce, unemployment, accident rates and suicide rates are all increased in PTSD sufferers. (Helzer et al, 1987;Hryvniak, 1989;Shore et al, 1989;Davidson et al, 1991;McFarlane and Papay, 1992;Davidson and Fairbank, 1993).…”
Section: General Backgroundmentioning
confidence: 99%
“…PTSD frequently does not occur in isolation but rather is accompanied by other personality disturbances. These conditions include antisocial personality disorder (Kulka et al, 1990), depression (Boman, 1986;Keane & Wolfe, 1990;Solomon, 1989;Hryvniak & Rosse, 1989;McKearn, 1988), bipolar disorder (Lucking, 1986), personality disorders (Keane & Wolfe, 1990), and obsessive-compulsive tendencies (Solomon, 1989).…”
Section: Models Supporting Predisposing Factors In Ptsdmentioning
confidence: 99%